Opinion Review of Socioeconomic Impact of COVID-2019 on Women's Health - Salami, Victory U.; Okoduwa, Stanley I. R.; Chris, Aimee O.; Ayilara, Susannah I.; Okoduwa, Ugochi J. (Frontiers in Global Women's Health, 2021)
The global battle to survive the onslaughts of the Coronavirus Disease 2019 (COVID-19) started in December 2019 and continues today. Women and girls have borne the brunt of the hardship resulting from the health crises. This paper examined the effects of COVID-19 on women. Socioeconomic factors resulting from the pandemic, especially in relation to women's health, were discussed after studying published articles. They include gender specificity and COVID-19, the economic toll of COVID-19 on women, pregnancy and COVID-19, gender-based violence due to COVID-19, and health-care impacts of COVID-19. Making up the majority in the healthcare workforce, women were at higher risk of infection with COVID-19 due to their exposure as caregivers to infected patients. The pandemic took its toll on them as part of the greater population in the informal sector of the economy due to the lockdown directive, as many experienced severe monetary shortages and job losses. Pregnant women infected with COVID-19 were prone to severe diseases, maternal complications, and death due to their weakened immunity and exposure during clinical procedures. Gender-based violence was observed to have increased across the globe for women. The results of this review strongly indicate that women are disproportionately affected by the ongoing COVID-19 health crisis. This review will help health-care professionals and policymakers arrive at properly-thought-through decisions to better manage health crises. Governments and all key players should address the challenge by devising effective policies with a gendered view.